SPIRAL OF SILENCE DI MEDIA SOSIAL: REINTERPRETASI TEORI KOMUNIKASI MASSA - Yessi Mareta Andari Putri; Intan Rachmina Koho; Ulfah; Asri Setiani; Andres Dharma Nurhalim; Chaerunnisa Al Syafitri (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study examines the Spiral of Silence phenomenon in the context of social media as a reinterpretation of mass communication theory in the digital era. The Spiral of Silence theory, proposed by Elisabeth Noelle-Neumann, explains the tendency of individuals to choose silence when their opinions are perceived as different or in the minority, in order to avoid social isolation. In traditional mass communication, the media plays a dominant role in shaping majority opinion. However, the development of social media has created a participatory, interactive, and algorithm-based communication space, giving rise to new dynamics in the formation of public opinion. Social media not only provides a space for expression but also creates social pressure through comments, likes, shares, and the potential for cyberbullying. This situation contributes to individuals' continued fear of social isolation, even within the seemingly free digital space. This study uses qualitative methods with a literature review approach to analyze how the Spiral of Silence operates in the social media environment and how mass communication theory needs to be reinterpreted in a digital context. The results show that the Spiral of Silence does not disappear on social media but instead undergoes a transformation. Individuals tend to engage in self-censorship, use anonymous accounts, or choose silence when confronted with dominant opinions. These findings confirm that social media continues to function as a mass communication medium with ideological power in shaping public opinion and individual communication behavior. Keywords: Spiral of Silence, Mass Communication, Social Media, Public Opinion